Bros - Weatherford, Carole Boston, 1956-; Brown, Reggie (Candlewick Press, 2024)
Celebrating boyhood and friendship, this upbeat picture book follows a group of young Black boys as they spend an adventure-filled day together living their best lives freely in their community.
Keywords: African Americans -- Juvenile fiction; Best friends -- Juvenile fiction; African Americans -- Fiction; Best friends -- Fiction; Stories in rhyme; Picture books; Stories in rhyme; Picture books